A study on assessing the knowledge and practices regarding indoor air pollution: The case of Magar community in Tahu, palpa. - Gautam, Kapil Prasad (2007)
SUMMARY: The study was conducted with an aim to assess the knowledge and practices of Magar community about Indoor Air Pollution (IAP) in Tahu VDC Ward No. one (1) of Palpa district. It was a descriptive (cross-sectional) type of study. Sampling technique and sample size both were purposive. A set of structured questionnaire were asked with the housewives of Magar HHs, who were mostly involved in cooking activities to find out their existing knowledge about the causes and consequence of IAP and the prevalent HH practices related to IAP. The study found that about 7 percent of the respondent housewives had good knowledge on causes of IAP whereas majority of them (about 73 percent) had poor knowledge on the possible health consequences attributable to IAP. Majority of the respondents (70 percent) replied that IAP is preventable but about 24 percent had no idea/knowledge about the possible preventive measures to mitigate the effects due to IAP. All the HHs were found to use biomass fuels for their cooking and heating purposes and fuel wood is the primary fuel used for cooking and heating purposes in all HHs. About 87 percent of the HHs was found to use electricity for lighting purpose. Only about 37 percent of H Hs was found to use improved cooking stove (ICS) for cooking, whereas 10 percent of HHs were found to have both traditional and ICS or biogas stove. Among ICS/biogas and the reason for not using ICS or biogas by majority (54 percent) was that they did not feel necessity. All the respondents were found to have the good practices of making fuel wood dry before use and keeping windows and door in the kitchen open during cooking. About 46 percent of the respondents having Under-five (U5) children were found to have the practice of accompanying their children during cooking time. 40 percent of the respondent housewives were found to expose in cooking activities fore more than 5 hours daily over 30 or more years. Overall 20 percent of the respondents had the history of having periods of cough, phlegm or breathlessness whereas about 64 percent of U5 children were found to from illness with cough and cold at any time within the past one year. All the respondents were found to seek the modern system of health care for treatment. Majority of HHs (80 percent) were indoor cooking, of which one-third had common or multipurpose kitchen at all. All the kitchens were found with visibly thick black soot or tar deposition on the ceiling and walls. 62.5 percent of the single purpose kitchens were found with adequate area. Of indoor cooking HHs, about 54 percent of the kitchens had got adequate ventilation in terms of window area per person. One-third of HHs was found to consume 15 kg or even more fuel wood per day. No illiterate respondents had good knowledge on causes and possible health problems related to IAP. Similarly, one-fourth of illiterate respondents had no knowledge about possible preventive measures for IAP. Proper dissemination of information and message about causes, effects and preventive measures is of great need in the community through the mobilization of community key persons and health workers of local level. For this, school teachers, community leaders, local health facility staffs and Village Development Committee (VDC) and community based organizations (CBOs) in raising awareness in the community about this ignored issue.